Positive education at all levels : learning to flourish - Tytherleigh, Michelle (Emerald Publishing Limited, 2024)
Positive education has grown and evolved, first as a discipline and then a perspective. Since its first wave of development as an application of positive psychology within education, where the focus was primarily on students, the second wave brought with it recognition of the importance of wellbeing for all those involved in education too. Now entering the third wave, with this comes positive education not as a discipline but as a perspective. In particular, a perspective which embraces the challenges of culture and diversity alongside already positively oriented programs, structures and frameworks within education that, with continued refinements, can bring out the best of what could be (Kern & Wehmeyer, 2021). With this third wave still in its infancy, therefore, Positive Education at all Levels brings the reader to where we are today, showcasing positive education across all three levels of UK education: primary, secondary, and tertiary. With chapters for parents as well as for educators, this book will be of interest for all those involved in positive education, including those who may be learners of positive education too.
Keywords: Education -- Great Britain.; Positive psychology.; Educational psychology.; Education -- Educational Psychology.; elektronické knihy; electronic books